2017
DOI: 10.1016/j.metabol.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde induces fat cell-autonomous thermogenesis and metabolic reprogramming

Abstract: Objective Cinnamaldehyde (CA) is a food compound that has previously been observed to be protective against obesity and hyperglycemia in mouse models. In this study, we aimed to elucidate the mechanisms behind this protective effect by assessing the cell-autonomous response of primary adipocytes to CA treatment. Methods Primary murine adipocytes were treated with CA and thermogenic and metabolic responses were assessed after both acute and chronic treatments. Human adipose stem cells were differentiated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 19 publications
1
33
0
2
Order By: Relevance
“…Contrarious to our data, cinnamon extract in IgE-stimulated human intestinal mast cells was reported to attenuate p38 phosphorylation 63 and p38 phosphorylation was significantly reduced in THP-1derived macrophages after treatment with trans-cinnamaldhyde, 28 whereas cinnamaldehyde was shown to induce phosphorylation of p38 in murine inguinal adipocytes. 64 In a LPSinduced acute lung injury mouse model, p-cymene revealed a dose-dependent significant mitigation of p38 phosphorylation. 54 Interestingly, the reported decrease of phospho-IκBα/ IκBα protein ratio after p-cymene treatment in the same study has been in line with our data.…”
Section: Food and Function Papermentioning
confidence: 97%
“…Contrarious to our data, cinnamon extract in IgE-stimulated human intestinal mast cells was reported to attenuate p38 phosphorylation 63 and p38 phosphorylation was significantly reduced in THP-1derived macrophages after treatment with trans-cinnamaldhyde, 28 whereas cinnamaldehyde was shown to induce phosphorylation of p38 in murine inguinal adipocytes. 64 In a LPSinduced acute lung injury mouse model, p-cymene revealed a dose-dependent significant mitigation of p38 phosphorylation. 54 Interestingly, the reported decrease of phospho-IκBα/ IκBα protein ratio after p-cymene treatment in the same study has been in line with our data.…”
Section: Food and Function Papermentioning
confidence: 97%
“…Going beyond the ability of spices to act as flavoring and antimicrobial agents [2], our studies show the broad-spectrum benevolence of spices through analysis of empirical data. Recent studies have shown the potential benefits of consumption of spices such as chillies through cohort studies [44] as well as the role of specific spice phytochemicals in their health effects [45]. Interestingly, the broad-spectrum benevolence score of a spice was not positively correlated with its phytochemical repertoire (S2 Fig) suggesting that richness in the phytochemical content itself does not explain its therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, cinnamon-linked increased rate of cold adaptive thermogenesis was due to the elevation in norepinephrine, blood levels of free fatty acid levels and increased expression of UCP1 in BAT [142]. Experimental studies have reported the ability of cinnamaldehyde in activating phospho-AMPK in adipose tissue [140], enhancing thermogenic and metabolic responses in human subcutaneous fat cells through a cAMP dependent protein kinase/p38 mitogen-activated protein kinase (p38 MAPK)-dependent pathway (involved in the transcription of thermogenic genes) [143] and inducing browning in mice subcutaneous adipocytes by increased expressions of UCP1 and other brown adipocyte markers and involvement of the β3-adrenoreceptor activity [144]. Finally, cinnamaldehyde has been shown to activate the transient receptor potential ankyrin 1 (TRPA1), an ion channel located at the cellular surface, acting as a mechanical and chemical stress sensor, which is involved in adrenalin secretion [145].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%